2013
DOI: 10.2147/opth.s53989
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal and macular thickness changes induced by cataract surgery

Abstract: BackgroundThe aim of this study was to evaluate the effect of uneventful phacoemulsification on the morphology and thickness of the macula, the submacular choroid, and the peripapillary choroid.MethodsIn 14 eyes from 14 patients, retinal macular thickness, choroidal submacular thickness, and choroidal peripapillary thickness were measured preoperatively and at one week and one month after phacoemulsification using enhanced depth imaging spectral domain optical coherence tomography. Changes in thickness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 22 publications
12
45
0
1
Order By: Relevance
“…They claimed that the inflammatory insult due to phacoemulsification mainly affects at the retinal level and seems to be independent of CT changes 23. By contrast; our results support the recent studies by Ohsugi et al24 and Noda et al,25 which report significant increases in CT after uneventful phacoemulsification.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They claimed that the inflammatory insult due to phacoemulsification mainly affects at the retinal level and seems to be independent of CT changes 23. By contrast; our results support the recent studies by Ohsugi et al24 and Noda et al,25 which report significant increases in CT after uneventful phacoemulsification.…”
Section: Discussionsupporting
confidence: 90%
“…Falcão et al23 evaluated the effect of uneventful phacoemulsification on the subfoveal CT and CMT, and they reported that phacoemulsification induced nonpathologic increases in CMT; however, these changes were not accompanied by significant changes in CT. They claimed that the inflammatory insult due to phacoemulsification mainly affects at the retinal level and seems to be independent of CT changes 23.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, it could be possible that the ocular inflammatory response to surgery could lead to changes in choroidal thickness. In patients without retinal disease, phacoemulsification does not lead to large variations in choroidal thickness, 17,29 and in our series we did not find any significant changes in choroidal thickness as far as SD-OCT can measure. This could be either because the inflammatory mediators released into an eye with a damaged external blood retinal barrier do not lead to vascular changes that can be detected by SD-OCT or because the intravitreal anti-VEGF blunts this possible response.…”
Section: -11supporting
confidence: 42%
“…13 Several authors have shown that even in patients without retinal pathology, phacoemulsification may lead to a subclinical increase in macular thickness. [15][16][17][18] Since exudative age-related macular degeneration is a vascular endothelial growth factor dependent disease cataract surgery could theoretically lead to a worsening of the CNV if the released VEGF is not antagonized.…”
Section: Introductionmentioning
confidence: 99%
“…However, it wouldn't have been ethical to study a control group without postoperative antiinflammatory agents to evaluate the true postcataract choroidal response. Falcao et al 20 did not find, in 14 eyes of 14 patients, any statistically significant changes in choroidal thickness 1 week or 1 month after uneventful cataract surgery. However, the number of patients included in their study is too small to come to a conclusion or counterbalance our own results.…”
Section: Discussionmentioning
confidence: 82%